KEPEMIMPINAN BERKELANJUTAN DALAM REVITALISASI KOTA LAMA SEMARANG TAHAP 1 - Masykurotur Rizqi Aji Putri; Kismartini Kismartini; Amni Zarkasyi Rahman (Journal of Public Policy and Management Review, 2021)
Kota Lama Semarang shows rapid changes where leadership is one of the factors of its success. Based on this, the researchers conducted research related to sustainable leadership as well as inhibiting and supporting factors for the success of the sustainable leadership model in the revitalization of Kota Lama Semarang phase 1. The results showed that the leader succeeded in taking his leadership so that there was rapid development. This is evidenced by analysis through the 5I Model for Sustainability Leadership and analysis of inhibiting and supporting factors. The rapid changes made the Kota Lama area have new challenges, so that the leader in this matter must be able to maintain the cultural values that exist in the Kota Lama Semarang.